2018
DOI: 10.3389/fphys.2018.01633
|View full text |Cite
|
Sign up to set email alerts
|

Marine Mammals’ NMDA Receptor Structure: Possible Adaptation to High Pressure Environment

Abstract: Divers that are exposed to high pressure (HP) above 1.1 MPa suffer from High Pressure Neurological Syndrome (HPNS), which is implicated with central nervous system (CNS) malfunction. Marine mammals performing extended and deep breath-hold dives are exposed to almost 20 MPa without apparent HPNS symptoms. N-methyl-D-aspartate receptor (NMDAR) has repeatedly been implicated as one of the major factors in CNS hyperexcitability as part of HPNS. Electrophysiological studies in rat brain slices at He HP showed a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…We confirmed using specific cRNA in three NMDAR subtypes that the glutamate dose-response curve and EC50 are not affected by HP He [51]. In addition, our investigations [30,51,52,[62][63][64] have demonstrated that aggregate formation, modified stoichiometry, and reversal potential alterations cannot explain the increase in the current of NMDAR containing the GluN2A subunit at HP He.…”
Section: Nmdar Characteristics: Affinity Stoichiometry Surface Expres...supporting
confidence: 75%
See 1 more Smart Citation
“…We confirmed using specific cRNA in three NMDAR subtypes that the glutamate dose-response curve and EC50 are not affected by HP He [51]. In addition, our investigations [30,51,52,[62][63][64] have demonstrated that aggregate formation, modified stoichiometry, and reversal potential alterations cannot explain the increase in the current of NMDAR containing the GluN2A subunit at HP He.…”
Section: Nmdar Characteristics: Affinity Stoichiometry Surface Expres...supporting
confidence: 75%
“…Taking this together with our MDS results, we can speculate that the presence of the He in diver breathing mixtures could partly contribute to HPNS symptoms. Another fact that may support this hypothesis is the ability of some marine mammals to perform very deep breath-hold dives when they are exposed only to hydrostatic pressure [62]. Our MDS study shows that pressure per se has a less devastating influence on the membrane and the embedded protein, which may render their CNS less vulnerable to ambient HP.…”
Section: Clinical Aspects and Considerationsmentioning
confidence: 60%
“…Organisms adapted to pressure include unicellular bacteria, archaea, eukaryotes as invertebrates and fishes and even deep diving marine mammals [79][80][81]. For example, in several hydrothermal vents have been found large invertebrates like mussels, crabs and shrimps and some marine mammals can dive exposed to almost 20 MPa without any negative symptom [82,83]. [8,102].…”
Section: Pressure Adaptation In Piezophilesmentioning
confidence: 99%
“…Few studies have been done on pressure adaptation of higher complex pluricellular organisms. For example, it is thought that the regulation of N-methyl-D-aspartate receptor (NMDR), a cell membrane protein found in nerve cells, is responsible for the absence of the high-pressure nervous syndrome (HPNS) on deep dive mammalians [83,112]. The regulation of this protein may be done by modulating its interaction with lipids, for example by the presence of cholesterol, and thanks to protein's particular tertiary structure in piezo-tolerant organisms.…”
Section: Pressure Adaptation In Piezophilesmentioning
confidence: 99%